The Trans-Hudson Orogen of North America and the Himalaya- Karakoram-Tibetan Orogen of Asia: Structural and thermal evolution of the collisional lower and upper plates - St-Onge, Marc; Searle, Michael; Wodicka, Natasha; van Gool, Jeroen; Garde, Adam; Scott, David (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1338 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.161